The Juridical Analysis of the Application of the rechtsverwerking Institution - Kusuma, Nadya Novina (Jurnal Konstatering, 2022)
This study aims to identify and analyze the mechanism for obtaining land rights through the rechtsverwerking institution and the application of rechtsverwerking in several court decisions that have permanent legal force. The research method used is juridical-normative by tracing secondary data through library research, while the analytical approach is carried out qualitatively with a prescriptive type. The results of the research show that the legal position of the rechtsverwerking institution in the land system in Indonesia is recognized and regulated in Article 32 of Government Regulation Number 24 of 1997 concerning Registration. With regard to the mechanism for acquiring land rights originating from old rights to land, the provisions contained in Article 24 of Government Regulation Number 24 of 1997 concerning Land Registration where rights to land originating from old rights are positioned as written evidence. to the existence of rights to a plot of land with the provision that it must pay attention to the terms of land tenure and also pay attention to the provisions of Article 32 paragraph (2). With regard to the acquisition of land rights through the rechtsverwerking institution, in the case of the Supreme Court Decision Number 1034 PK/Pdt/2019, it shows that there is still a lack of uniformity in understanding by the judges regarding the position of land rights originating from old land rights and the mechanism for obtaining land rights through the rechtsverwerking agency.Keywords: Land; Rechtverwerking; National.